Late Pulmonary Toxicity Associated With Everolimus in a Renal Transplant Patient and Review of the Literature - VELİOĞLU, ARZU; TUĞLULAR, ZÜBEYDE SERHAN (BASKENT UNIV, 2018)
The use of inhibitors of mammalian target of rapamycin is associated with adverse pulmonary effects. Although sirolimus-related pneumonitis has been well described, reports on pneumonitis with everolimus are scarce. We report a case of everolimus-induced pneumonitis in a renal transplant recipient 5 years after initiation of everolimus treatment, and we also review the literature regarding everolimus-induced pneumonitis in renal transplant patients.
Keywords: Everolimus; Kidney; Pneumonitis; Transplant; SINGLE-CENTER EXPERIENCE; PHASE-III TRIAL; INTERSTITIAL PNEUMONITIS; ALLOGRAFT RECIPIENTS; MAMMALIAN TARGET; CELL CARCINOMA; KIDNEY; SIROLIMUS; INHIBITORS; CONVERSION